A T Cell View of the Bone Marrow - Bonomo, Adriana; Monteiro, Ana Carolina; Gonçalves-Silva, Triciana; Cordeiro-Spinetti, Eric; Galvani, Rômulo Gonçalves; Balduino, Alex (Frontiers in Immunology, 2016)
The majority of T cells present in the bone marrow (BM) represent an activated/memory phenotype and most of these, if not all, are circulating T cells. Their lodging in the bone marrow keeps them activated, turning the bone marrow microenvironment into a “memory reservoir”. This article will focus on how T cell activation in the marrow results in both direct and indirect effect on the hematopoiesis. The hematopoietic stem cell niche will be presented, with its main components and organization, along with the role-played by T-lymphocytes in basal and pathologic conditions and their effect on the bone remodeling process. Also discussed herein will be how “normal” bone mass peak is achieved only in the presence of an intact adaptive immune system, with T and B cells playing critical roles in this process. Our main hypothesis is that the partnership between T cells and cells of the bone marrow microenvironment orchestrates numerous processes regulating immunity, hematopoiesis and bone remodeling.